New approach to the mitral valve through the left anterior minithoracotomy for combined valve and coronary surgical proceduresCentral MessagePerspective - Oleksandr Babliak, MD, PhD; Vasyl Lazoryshynets, MD, PhD; Volodymyr Demianenko, MD, PhD; Dmytro Babliak, MD; Anton Marchenko, MD; Katerina Revenko, MD; Yevhenii Melnyk, MD; Oleksii Stohov, MD (JTCVS Techniques)
Objective: We have developed a new technique for accessing the mitral valve through the left anterior minithoracotomy. This approach has been used in patients requiring both mitral valve surgery and coronary artery bypass grafting. Methods: From October 2020 to September 2022, we performed 24 concomitant mitral valve procedures and coronary artery bypass grafting through the left anterior minithoracotomy. The average age of the patients was 65.5 years, and the mean left ventricular ejection fraction was 44.5%. Computed tomography angiography was routinely performed preoperatively. The surgical technique included a left anterior minithoracotomy in the fourth intercostal space, peripheral cardiopulmonary bypass, aortic crossclamping using a transthoracic clamp through the additional port in the left second intercostal space, the administration of cold blood cardioplegia, a right atrial transseptal approach to the mitral valve, and special surgical exposure maneuvers. These maneuvers were designed to displace the heart into the left pleural space by pulling the inferior vena cava tape and the ascending aorta tape to the left. Conventional mitral valve surgical techniques were used. The mitral valve repair or replacement was performed after the distal anastomoses to the right and circumflex coronary system were completed. Subsequently, after the mitral valve procedure, coronary anastomosis to the left anterior descending artery was performed. Results: The mitral valve was effectively visualized, and a planned procedure was successfully completed in all patients. There was no need for conversion to a sternotomy. mitral valve repair was performed in 22 patients (91.7%), and mitral valve replacement was performed in 2 patients (8.3%). Conventional surgical instruments were used in 10 cases (41%), and long-shafted instruments were used in 14 cases (59%). A knot-pusher was required in 9 cases (37.5%). A computed tomography distance from the skin level to the mitral valve posterior annulus of more than 14 cm was identified as a technical difficulty marker, necessitating the use of long-shafted instruments. Concomitant complete revascularization was achieved in all cases. The mean number of distal anastomoses was 2.54 ± 0.7 (1; 4). Total operation time was 341 ± 41 (285; 420) minutes, cardiopulmonary bypass time was 231 ± 38 (172; 316) minutes, and the crossclamp time was 127 ± 23 (80; 169) minutes. Patients had a mean intensive care unit stay of 1.87 ± 0.69 (1; 4) days, and their total hospital stay averaged 6.54 ± 1.86 (4; 10) days. There were no reoperations due to bleeding, no occurrences of strokes, and no other major complications. There were no instances of hospital mortality or mortality within 30 days after the procedures. Conclusions: Mitral valve repair or replacement through the left anterior thoracotomy and transseptal approach is a valuable and effective technique that can be used for concomitant procedures performed through a single minithoracotomy incision in selected patients.